Cefotaxime induced generalized bullous fixed drug eruption - A case report - R. Manikandan; A. Porselvi; G.C. Keerthana; K. Vaishnavi; S. Girija; Murali Narasimhan; TM. Vijayakumar (Toxicology Reports, 2018)
Fixed drug eruption (FDE) is the most common cutaneous adverse drug reaction. Cefotaxime, a broad-spectrum third-generation cephalosporin, appeared to be a safe and effective therapy in greater than 90% of infections including cellulitis, abscesses and necrotizing ulcers of the skin and subcutaneous tissues but here we report a rare case of 36 years old female patient developed generalized bullous FDE after intravenous administration of Cefotaxime. Keywords: Cefotaxime, Fixed drug eruption, Antibiotic, Dermatology